2005
DOI: 10.1021/ef049809d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Solvent Effects on Asphaltene Dimers

Abstract: Asphaltene deposition is a well-known problem in the petroleum industry. Nevertheless, there seems to be a lack of information on the processes involved in asphaltene association and its relationship to asphaltene solubility under certain conditions. Molecular mechanics and molecular dynamics have had an important role in the investigation of these phenomena. To better understand the role of solvents in fractionating asphaltenes extracted from vacuum residues and evaluate their tendency to dissociate under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 28 publications
5
70
0
5
Order By: Relevance
“…In most previous studies only one or a few model structures used were consistent with experimental data. [34] In this work, using molecular dynamics simulation, the solubility of all 28 proposed asphaltene molecular structures with molecular masses ranging from 500-2000 g/mol in common solvents have been studied, and the results indicated that the solubility is related to the asphaltenes' molecular structure. Additionally, the relationship between solubility parameter, density, and asphaltenes' molecular structure was investigated and the solubility of asphaltenes was discussed on the basis of the obtained results.…”
Section: Introductionmentioning
confidence: 94%
“…In most previous studies only one or a few model structures used were consistent with experimental data. [34] In this work, using molecular dynamics simulation, the solubility of all 28 proposed asphaltene molecular structures with molecular masses ranging from 500-2000 g/mol in common solvents have been studied, and the results indicated that the solubility is related to the asphaltenes' molecular structure. Additionally, the relationship between solubility parameter, density, and asphaltenes' molecular structure was investigated and the solubility of asphaltenes was discussed on the basis of the obtained results.…”
Section: Introductionmentioning
confidence: 94%
“…4,6,7 The profile of the asphaltenes separated during refining depends on the type of crude oil, its origin and the type and quantity of flocculating agent added during the process, in the last case expressed as the flocculant/oil ratio. 8,9 The structure of asphaltenes is formed by aromatic polycondensate nuclei linked to the cyclical and aliphatic chains, containing heteroatoms such as oxygen, nitrogen and sulfur along with metals including iron, vanadium and nickel. Their exact structure is unknown due to the variety and complexity of their chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Asfaltenos podem ser definidos por seu comportamento na presença de solventes, solúveis em solventes aromáticos, permanecendo insolúvel em compostos alifáticos (Carauta et al 2005). A fracção de asfaltenos é composta por muitas moléculas de diferentes pesos moleculares e polaridades que têm as mesmas propriedades de solubilidade no solvente.…”
Section: Introductionunclassified
“…O modelo utilizado para representar as moléculas de asfalteno foi desenvolvido no trabalho de Carauta et al 2005, e para validar o processo da simulação molecular, os dados do comportamento do dímero com tolueno e heptano foram reproduzidos. Feito isso, foi possível desenvolver as simulações com solventes alternativos.…”
Section: Introductionunclassified